Antiplasticization and phase behavior in phase-separated modified starch-sucrose blends: A positron lifetime and solid-state NMR study. (15th December 2020) - Martini, Francesca; Hughes, David J.; Badolato Bönisch, Gabriela; Zwick, Thomas; Schäfer, Christian; Geppi, Marco; Alam, M. Ashraf; Ubbink, Job
Graphical abstract: Highlights: Structure & dynamics of phase-separated modified starch-sucrose blends are explored. 13 C NQS NMR allows to quantify the distribution of sucrose over the phases. Positron lifetime and solid-state NMR confirm antiplasticization of starch by sucrose. Spin diffusion NMR indicates that starch domains are very small (～ 5 nm). Observed antiplasticization and phase separation impact physical stability. Abstract: Interactions, organization and dynamics within phase-separated ternary blends of hydrophobically modified starch (HMS), sucrose and water are investigated using solid-state NMR and positron annihilation lifetime spectroscopy (PALS). Antiplasticization of HMS by sucrose is demonstrated by PALS and 1 H NMR T 1 measurements. Selective solid-state 13 C NMR experiments show that a large fraction of sucrose is in molecular contact with HMS even at high sucrose contents, indicating that the HMS-sucrose phase separation is only partial. Sucrose is observed to migrate away from the HMS-rich domains at temperatures that are above the lower T g, but still below the upper T g . 1 H spin diffusion experiments indicate that phase separation occurs on a nanometric scale, in line with recent theory (Van der Sman, Food Hydrocolloids 87, 360–370 (2019)). We infer that the nanoscale structure of the HMS-rich phase allows for intimate molecular contact between the HMS-rich and the sucrose-rich phases and explains the unusual dynamic behavior.